Multifunctional Utilization of Pitch‐Coated Carbon Fibers in Lithium‐Based Rechargeable Batteries. Issue 17 (12th March 2021) - Ghosh, Shuvajit; Bhattacharjee, Udita; Patchaiyappan, Sivaraman; Nanda, Jagjit; Dudney, Nancy J.; Martha, Surendra K.
Abstract: This work reports carbon fibers as an electrode material and current collector for dual‐carbon and lithium‐ion batteries. Fully graphitic and semigraphitic carbon fibers undergo anion intercalation beyond 4.5 V versus Li/Li + . Symmetric dual‐carbon full cells using a pitch‐coated fully graphitic carbon fiber mat as both cathode and anode delivers an energy‐density of 276 and 322 Wh kg −1 at 342 W kg −1 power density in the voltage range of 3.0–5.0 and 3.0–5.2 V, respectively. On the other hand, nongraphitic carbon fibers do not exhibit anion intercalation up to 5.2 V and can be used as a current collector. They also possess a larger number of Li + storage sites in their randomly oriented microstructure when used as an anode. A lithium‐ion full cell with double carbon‐coated C‐LiFePO4 loaded on nongraphitic carbon fiber as a cathode and pitch‐coated nongraphitic carbon fiber as an anode exhibits 202.6 and 75.2 Wh kg −1 energy density at power densities of 46.75 W kg −1 and 11.7 kW kg −1, respectively in 2.0–3.5 V range. This pitch‐coated carbon fiber‐based battery configuration eliminates the need for metal foils and costly fluorinated binders, lowers overall weight of the cell, and is capable of sustaining mechanical stress and thermal shock. Abstract : This work demonstrates that P‐pitch‐coated carbon fibers have multifaceted utility as electrode active materials and current collectors for binder‐free and metal current collector‐free lithium‐based dual carbon batteries (DCBs) and lithium‐ion batteries (LIBs). The existence of graphitic domains determines their anion storage capabilities and efficacies as stable current collectors at higher voltages and thus governs their functionality in DCBs and LIBs.